Distribution and Diversity of Seagrass Types in the Amahai And Sehati Waters of Central Maluku Regency - Masihu, Junardin Muhamad; Melsasail, Karel M.; Aloatuan, Febiayu; Elly, Sovian S.; Rumengan, Yuliana (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
Amahai and Sehati are located in Central Maluku Regency, Maluku Province, which has a diversity of seagrass species spread across the intertidal and subtidal zones. The purpose of this study was to determine (1) the distribution of seagrass in the intertidal and subtidal zones, (2) the diversity value of seagrass species in the intertidal and subtidal zones. The study was conducted from 8 to 21 December 2024 using the linear quadrat transect method. 3 transects were made in Amahai waters and 5 transects in Sehati waters. Each transect consisted of 10 quadrats measuring 1x1 meter. The study found 3 types of seagrass, namely Cymodocea serrulata, Halodule pinifolia, and Halophila ovalis in the intertidal zone and Enhalus acoroides and Thalassia hemprichii seagrass species were found in the subtidal zone. The Physico-Chemical Factors of Amahai waters in the intertidal zone found seawater temperature of 280C, salinity of 27.40/00, and pH of 7.4. The Physico-Chemical factors of Amahai waters in the subtidal zone are, temperature 280C, salinity 29.10/00, and pH 7.3. The average physico-chemical factors in the tidal zone in Sehati coastal waters are, sea air temperature of 290C, salinity of 26.50/00, and sea air pH of 7.5. The average physico-chemical factors in the subtidal zone of Amahai waters are, temperature 290C, salinity 28.40/00, and pH 7.5. The distribution pattern of seagrass in the intertidal and subtidal zones in Amahai and Sehati waters is relatively even. The value of the seagrass species diversity index in the tidal zone of Amahai (1.487) and Sehati waters (1.359) is classified as moderate. The value of the seagrass species diversity index in the subtidal zone of Amahai (0.675) and Sehati (0.693) is classified as moderate. This research contributes to the coastal ecosystem to improve the welfare of the community around Amahai Village and Sehati Village.